Analisis Motivasi Kerja, Insentif, Dan Lingkungan Kerja Terhadap Kinerja Pegawai Di Dinas Pendidikan Dan Kebudayaan Kabupaten Jombang - Abdul Majid; Abu Talkah (Universitas Islam Kadiri, 2021)
The performance of each employee is different from other employees according to the level of knowledge, skills and motivation possessed by the employee. The management of human resource management which is carried out in a professional manner can improve employee performance. The purpose of this study was to determine the significance of the effect of work motivation, incentives, and work environment on employee performance. Data research techniques in this study are Questionnaire/Questionnaire, Observation, and Documentation techniques. Data Quality Test using Validity and Reliability Test. The data analysis technique uses Multiple Linear Regression Analysis, F-Test, T-Test, and calculates the Coefficient of Determination (R2). Based on the results of statistical analysis, it can be explained that the effect of work motivation on employee performance has a sig value. 0.000<0.05. The effect of the incentive variable on employee performance has a value of sig.0,000 <0.05. The effect of work environment variables on performance has a value of sig. 0.016> 0.05. From these results it can be concluded that the variables of motivation, incentives, and work environment have a significant influence on the performance of the Education and Culture Office of Jombang Regency.